The History of Indonesian Capital Market - Sumawijaya, Ahmad Ghani (Anthology: Inside Intellectual Property Rights, 2025)
This paper will primarily talk about the historical development of the Indonesian capital market from colonial, which is the era of the Dutch East Indies (for Indonesia specifically, from the 17th century to 1,949) to modern times. It begins by looking at the first stock market in Batavia, which became operational during the Dutch East Indies government, showing its early problems/issues and its collapse. The conversation then follows another historic event for the Indonesian capital market during President Soeharto's New Order era, pointing out important events like major positive impacts of development, such as the reactivation of the Jakarta Stock Exchange and the release of important laws and systems. The research also looks at the changes in institutions that affect transformation in the law/and legislative improvement that took place in the 1990s, as well as what came after the merger of Indonesian stock exchanges. The study uses a historical perspective or the lens of history to show/explain how economic and political developments have a huge impact on regulation changes and the development of Indonesia's capital markets. The paper continues by pointing out the important part of strong legal systems and control for keeping an effective and open capital market.